2014
DOI: 10.1038/nnano.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of single mRNA splice variants in living cells

Abstract: Alternative mRNA splicing is a fundamental process of gene regulation via the precise control of the post-transcriptional step that occurs before mRNA translation. Errors in RNA splicing have been known to correlate with different diseases; however, a key limitation is the lack of technologies for live cell monitoring and quantification to understand the process of alternative splicing. Here, we report a spectroscopic strategy for quantitative imaging of mRNA splice variants in living cells, using nanoplasmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
136
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 50 publications
1
136
0
1
Order By: Relevance
“…4 The nanoprobes are capable of hybridizing to the transcripts with a very broad range of sequences as long as sequence specificity is ensured for transcript targeting. 41 Quantification of mRNA molecules in breast cancer tissues is much lower than that in SK-BR-3 cells, while it is comparable to the number in MCF-7 cells, 30,39 and is in agreement with previous publications. 42 There is large variation in the expression level of Her2 in different cell lines.…”
Section: 40supporting
confidence: 91%
“…4 The nanoprobes are capable of hybridizing to the transcripts with a very broad range of sequences as long as sequence specificity is ensured for transcript targeting. 41 Quantification of mRNA molecules in breast cancer tissues is much lower than that in SK-BR-3 cells, while it is comparable to the number in MCF-7 cells, 30,39 and is in agreement with previous publications. 42 There is large variation in the expression level of Her2 in different cell lines.…”
Section: 40supporting
confidence: 91%
“…Localized surface plasmon resonances (LSPR) of plasmonic nanostructures have strong extinction, scattering, and absorption properties are dimension tunable 812 and could serve as potential sensor substrates for label-free sensing of a range of targets. It has also been shown that near-field enhancements at the sharp plasmonic edges and strengthening of inter-particle optical coupling, critical for signal enhancement can be observed due to LSPR 13 . LSPR has been exploited to develop highly sensitive biological assays, molecular imaging, photodynamic therapy, drug delivery, and surface-enhanced Raman spectroscopy (SERS).…”
mentioning
confidence: 99%
“…35-37 To uncover epigenomic heterogeneity, modern optical microscopy provides elegant solutions for inspecting a single cell. 18, 38, 39 …”
Section: Discussionmentioning
confidence: 99%
“…18, 19 Owing to the dipole resonance from the interaction with incident photons, the large scattering cross-section of metal NPs can generate a ten- to million-fold stronger signal than conventional fluorophores, 20, 21 providing a high SNR without laser excitation. Besides, the LSPR spectrum can be fine-tuned, dependent on the NP size, shape, material, and surrounding environment.…”
Section: Introductionmentioning
confidence: 99%